Coupled influence of pore defects on the failure site for high-speed railway gearbox material. (15th February 2022) - Liu, Pengfei; Wang, Chenlong; Yang, Shaopu; Jiao, Yinan; Li, Xiaowei; Li, Hefei; Zhang, Yang; Liu, Yongqiang; Wu, Shengchuan; Zhao, Jinjin
Highlights: A coupling factor considering the effective volume and diameter, f, is proposed to describe the competitive effect. Fatigue specimens mostly fail at the pore with the largest f . Fatigue crack propagation rates exhibit a linear relationship with the coupling factor, when it exceeds 2. The geometry features of pores, as well as the orientations of ellipsoid pores are insignificant compared with pore size and pore location. Abstract: The high-speed railway gearbox has been found with fatigue cracks during routine operation, which may induce oil leakage and present a serious safety hazard. Porosity has been often reported to have the greatest propensity for acting as a fatigue crack initiation site in cast Al alloys. Herein, fatigue resistance of cast Al gearboxes has been investigated using high-resolution synchrotron X-ray computed tomography based on an in-situ fatigue. A coupling factor (f) is described as the effective radius divided by deviation length, is proposed to describe the coupling behavior of pore size and pore location, which correlate well with experimental results. Crack propagation rates show a linear relationship with f. The pore with the highest f value has a crack propagation rate of 4.06 × 10 -4 μm/cycle, whereas the largest pore, with an f value of 0.86, only has a crack propagation rate of 1.55 × 10 -5 μm/cycle. The coupling factor can be applied to predict the failure position of high-speed railway gearbox materials.